Formulasi Rencana Pembangunan Jangka Menengah Desa (RPJMDes) Buluh Cina Kecamatan Siak Hulu Kabupaten Kampar Tahun 2011-2015 - Auradian Marta; Khairul Anwar; Hery Suryadi (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
This research aims to describe of process or mechanism and formulation model of RencanaPembangunan Jangka Menengah Desa (RPJMDes) Buluh Cina 2011-2015. This research is descriptivetype with used qualitative method. The data on this research obtained are depth interview with informanand documentation study. From this research obtained result that on formulation Rencana PembangunanDesa (RPJMDes) Buluh Cina 2011-2015 pass through Musrenbangdes. Musrenbangdes involved allcomponent participation from institutional and the people. Thus, in formulation RPJMDes used democraticmodel.Keywords: formulation, democratic model, RPJMDes